Case report: Diagnostic clues for anti-3-hydroxy-3-methylglutaryl-coenzyme A reductase myopathy in pediatric patients - Watanuki, Keisuke; Koga, Hiroshi (Frontiers in Pediatrics, 2023)
Introduction Anti-3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) myopathy is a recently recognized pathology, but appears less common in children and the characteristics of pediatric cases remain unclear. Case report We report a pediatric case of anti-HMGCR myopathy accompanied by skin rash. Motor function and serum creatine kinase level normalized after combinational treatment including early intravenous immunoglobulin, methotrexate, and corticosteroid. Literature review We searched PubMed and identified reports with detailed clinical information of 33 pediatric patients <18 years old with anti-HMGCR myopathy. Among these 33 patients and our own case, skin rash and maximum serum creatine kinase level >5,000 IU/L were observed in 44% (15 patients) and 94% (32 patients), respectively. Skin rash was present in 15 of the 22 patients (68%) ≥7 years old and none of the 12 patients (0%) <7 years old. Among the 15 patients with skin rash, 12 (80%) presented with erythematous rash. Conclusion Erythematous skin rash may offer a clue to the diagnosis of anti-HMGCR myopathy in children with muscle weakness and serum creatine kinase level >5,000 IU/L in the absence of other myositis-specific antibodies, particularly in patients ≥7 years old. Our results suggest the importance of early anti-HMGCR testing in pediatric patients with these manifestations.